The Level of Total Sialic Acid In Patients With Typhoid Fever - Al-Assady, Z. T (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this research is to shed some light on the level ofserum total sialic acid (TSA) in individuals with typhoid fever. The individuals were at age of (35-45) years old and (TSA) was measured by resorcinol reagents. The results showed significant reduction in (TSA) compared to control or normal individuals.